Analysis of School Management Readiness to Face-to-Face Learning at SMA Negeri 1 Kayuagung OKI Regency - Sulastri, Sulastri; Fitria, Happy; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to describe and find out the Analysis of School Management Readiness, Constraints, and Solutions to Face Face-to-Face Learning at SMA Negeri 1 Kayuagung, OKI Regency. Data collection tools using interviews, documentation, observation and literature review. Data analysis used descriptive qualitative analysis with research stages referring to Miles and Huberman’s theory, namely data collection, data reduction, data presentation, drawing conclusions. The results of the study stated that school management facing face-to-face learning at Kayuagung 1 Public High School was carried out through 1) planning face-to-face learning preparation after online learning; 2) organizing school resources to carry out face-to-face learning after online learning; 3) carrying out face-to-face learning; 4) supervise the implementation of face-to-face learning at SMA Negeri 1 Kayuagung. The obstacles faced are 1) Compliance with health protocols; 2) The number of students exceeds the capacity of the classroom; 3) Availability of resources and equipment; 4) Uncertainty of the pandemic situation; 5) Adjustment of teaching methods; 6) Limited internet access The solutions taken include 1) Providing training and education to students, teachers, staff and parents regarding the importance of complying with health protocols; 2) Carry out regular monitoring and evaluation of the implementation of face-to-face learning; 3) Maintain strict health protocols.